2016
DOI: 10.1159/000443703
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Motif Protein 72 Regulates the Proliferation and Migration of Rat Cardiac Fibroblasts via the Transforming Growth Factor-β Signaling Pathway

Abstract: Background: The proliferation and migration of cardiac fibroblasts are critical for the progress of cardiac fibrosis. Tripartite motif protein 72 (Trim72), also known as MG53, mediates the dynamic process of membrane fusion and exocytosis in striated muscle. However, the role of Trim72 in the proliferation and migration of cardiac fibroblasts is unknown. Methods: In the present study, we used small interference RNA (siRNA) to silence Trim72 and then investigated the effects of Trim72 on cardiac fibroblast prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Primary cardiac fibroblasts (CFs) were isolated from 1 to 3-day-old Sprague-Dawley rats purchased from the Experimental Animal Center of Nanjing University of Traditional Chinese Medicine as described previously [31]. CFs were cultured in DMEM containing 10 % fetal bovine serum (FBS), 100 U/ml penicillin, and 100 ug/ml streptomycin at standard culture conditions (37 °C, with 5 % CO2).…”
Section: Methodsmentioning
confidence: 99%
“…Primary cardiac fibroblasts (CFs) were isolated from 1 to 3-day-old Sprague-Dawley rats purchased from the Experimental Animal Center of Nanjing University of Traditional Chinese Medicine as described previously [31]. CFs were cultured in DMEM containing 10 % fetal bovine serum (FBS), 100 U/ml penicillin, and 100 ug/ml streptomycin at standard culture conditions (37 °C, with 5 % CO2).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, down regulated genes such as KHSRP, TRIM72, MLLT1, C3 and DDIT4 were identified as target genes showing the highest number of integration with miRNAs. Low expression of TRIM72 was responsible for development of cardiovascular diseases [113], but loss of this gene may be linked with progression of CAD. In this network down regulated genes such as KH-type splicing regulatory protein (FUSE binding protein 2) (KHSRP), MLLT1 and DDIT4 along with miRNA such as hsa-mir-548ac, hsa-mir-6890-3p, hsa-mir-5681a, hsa-mir-3135b and hsa-mir-3607-3p were predicted as novel prognostic or diagnostic biomarkers and new therapeutic target in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and Lei [51] found, for the first time, that a reduction in TRIM72 in rat cardiac fibroblasts downregulated the TGF-β1/Smad signaling pathway, thus inhibiting the proliferation and migration of the cardiac fibroblasts, causing subsequent changes in the extent of cardiac fibrosis. Chen et al [52] found that TRIM72 induces fibroblast proliferation and promotes fibroblastto-myofibroblast transition by suppressing the STAT3/ Notch-1 pathway.…”
Section: Color Version Available Onlinementioning
confidence: 99%